2016
DOI: 10.19082/2833
|View full text |Cite
|
Sign up to set email alerts
|

A multi-strain Synbiotic may reduce viral respiratory infections in asthmatic children: a randomized controlled trial

Abstract: Background and objectiveAsthma is a growing problem worldwide. Acute exacerbations impose considerable morbidity, mortality, and increased cost. Viral respiratory infections are the most common cause (80–85%) of pediatric asthma exacerbations and admissions to the hospital. The aim of this study was to determine the effect of a new synbiotic Lactocare® on viral respiratory infections and asthma exacerbations in asthmatic children.MethodsIn this double blind, placebo-controlled, randomized clinical trial, 72 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…There may be side effects of probiotics in patients with critical illness or bone marrow/stem cell transplantation . One included study reported that probiotics might not significantly increase the incidence of fever and diarrhoea . Among all included RCTs, rare cases of severe complications occurred, with a certain association with probiotics consumption.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There may be side effects of probiotics in patients with critical illness or bone marrow/stem cell transplantation . One included study reported that probiotics might not significantly increase the incidence of fever and diarrhoea . Among all included RCTs, rare cases of severe complications occurred, with a certain association with probiotics consumption.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the use of bronchodilators were inconsistent in different studies. Two studies 12,16 showed that the frequency was statistically reduced after probiotics supplementation. However, Rose et al 17 indicated that there was no significant difference when using inhalative betamimetics during the daytime in two arms.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations